2020
DOI: 10.33988/auvfd.658135
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk in public parks: Investigation of the tick species (Acari: Ixodida) in Bursa metropolitan area, Turkey

Abstract: Ticks feed on a wide variety of mammals, birds, reptiles, and even amphibians. The majority of ticks choose specific animal species that are of no medical or veterinary importance for feeding, while others grasp a wide range of hosts, such as petbreeding animals or humans. They can also transmit many human and animal pathogens include viruses, bacteria, rickettsia and protozoa in Turkey. This study was carried out to detect the distribution of ticks in public parks in six districts (Osmangazi, Yıldırım, Nilüfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This is indicated by the differences in the seasons of activity of the tick (spring and autumn months in the northern part of the range (Filippova, 1977) and winter months in our observations and in those by Yeruham et al (1995), and by its preferential occurrence in the areas characterized by higher humidity and lower sun irradiation in our and Yeruham's observations. A bimodal activity pattern with a strong decline of activity in January observed in our survey is also common to I. ricinus near the southern border of its range (Daniel et al, 2015;Aydin et al, 2020). Our data allow to estimate the average daily maximal air temperatures in the range of 13-20°C as optimal for activity of adult I. eldaricus.…”
Section: Discussionsupporting
confidence: 64%
“…This is indicated by the differences in the seasons of activity of the tick (spring and autumn months in the northern part of the range (Filippova, 1977) and winter months in our observations and in those by Yeruham et al (1995), and by its preferential occurrence in the areas characterized by higher humidity and lower sun irradiation in our and Yeruham's observations. A bimodal activity pattern with a strong decline of activity in January observed in our survey is also common to I. ricinus near the southern border of its range (Daniel et al, 2015;Aydin et al, 2020). Our data allow to estimate the average daily maximal air temperatures in the range of 13-20°C as optimal for activity of adult I. eldaricus.…”
Section: Discussionsupporting
confidence: 64%
“…More than 40 tick species have been reported in the country to date [191]. The most-recorded species were H. marginatum, Hyalomma excavatum, Hyalomma anatolicum, Hyalomma asiaticum, Hyalomma aegyptium, R. sanguineus s.l., Rhipicephalus turanicus, Rhipicephalus bursa, Haemaphysalis parva, and Dermacentor marginatus [192][193][194][195][196][197][198]. As a result of this tick species richness, a number of pathogens have been detected, including Ehrlichia canis, Theileria spp.…”
Section: Turkeymentioning
confidence: 99%
“…Latreille (Acari: Ixodidae) is known as the brown dog tick and acts as a vector for zoonotic disease pathogens such as Rickettsia conorii, Ehrlichia canis, and Coxiella burnetii [12]. The prevalence of these ticks in urban areas and parks raises concerns about human and animal health [13,14]. Unfortunately, recent studies have shown that Rhipicephalus ticks have developed resistance to chemical acaricides used by pet owners to protect against ticks in parks and gardens [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%